Respuesta :

Answer:

The idea is to transform the expression by multiplying [tex](\sqrt{x + 1} - \sqrt{x})[/tex] with its conjugate, [tex](\sqrt{x + 1} + \sqrt{x})[/tex].

Step-by-step explanation:

For any real number [tex]a[/tex] and [tex]b[/tex], [tex](a + b)\, (a - b) = a^{2} - b^{2}[/tex].

The factor [tex](\sqrt{x + 1} - \sqrt{x})[/tex] is irrational. However, when multiplied with its square root conjugate [tex](\sqrt{x + 1} + \sqrt{x})[/tex], the product would become rational:

[tex]\begin{aligned} & (\sqrt{x + 1} - \sqrt{x}) \, (\sqrt{x + 1} + \sqrt{x}) \\ &= (\sqrt{x + 1})^{2} -(\sqrt{x})^{2} \\ &= (x + 1) - (x) = 1\end{aligned}[/tex].

The idea is to multiply [tex]\sqrt{x}\, (\sqrt{x + 1} - \sqrt{x})[/tex] by [tex]\displaystyle \frac{\sqrt{x + 1} + \sqrt{x}}{\sqrt{x + 1} + \sqrt{x}}[/tex] so as to make it easier to take the limit.

Since [tex]\displaystyle \frac{\sqrt{x + 1} + \sqrt{x}}{\sqrt{x + 1} + \sqrt{x}} = 1[/tex], multiplying the expression by this fraction would not change the value of the original expression.

[tex]\begin{aligned} & \lim\limits_{x \to \infty} \sqrt{x} \, (\sqrt{x + 1} - \sqrt{x}) \\ &= \lim\limits_{x \to \infty} \left[\sqrt{x} \, (\sqrt{x + 1} - \sqrt{x})\cdot \frac{\sqrt{x + 1} + \sqrt{x}}{\sqrt{x + 1} + \sqrt{x}}\right] \\ &= \lim\limits_{x \to \infty} \frac{\sqrt{x}\, ((x + 1) - x)}{\sqrt{x + 1} + \sqrt{x}} \\ &= \lim\limits_{x \to \infty} \frac{\sqrt{x}}{\sqrt{x + 1}+ \sqrt{x}}\end{aligned}[/tex].

The order of [tex]x[/tex] in both the numerator and the denominator are now both [tex](1/2)[/tex]. Hence, dividing both the numerator and the denominator by [tex]x^{(1/2)}[/tex] (same as [tex]\sqrt{x}[/tex]) would ensure that all but the constant terms would approach [tex]0[/tex] under this limit:

[tex]\begin{aligned} & \lim\limits_{x \to \infty} \sqrt{x} \, (\sqrt{x + 1} - \sqrt{x}) \\ &= \cdots\\ &= \lim\limits_{x \to \infty} \frac{\sqrt{x}}{\sqrt{x + 1}+ \sqrt{x}} \\ &= \lim\limits_{x \to \infty} \frac{\sqrt{x} / \sqrt{x}}{(\sqrt{x + 1} / \sqrt{x}) + (\sqrt{x} / \sqrt{x})} \\ &= \lim\limits_{x \to \infty}\frac{1}{\sqrt{(x / x) + (1 / x)} + 1} \\ &= \lim\limits_{x \to \infty} \frac{1}{\sqrt{1 + (1/x)} + 1}\end{aligned}[/tex].

By continuity:

[tex]\begin{aligned} & \lim\limits_{x \to \infty} \sqrt{x} \, (\sqrt{x + 1} - \sqrt{x}) \\ &= \cdots\\ &= \lim\limits_{x \to \infty} \frac{\sqrt{x}}{\sqrt{x + 1}+ \sqrt{x}} \\ &= \cdots \\ &= \lim\limits_{x \to \infty} \frac{1}{\sqrt{1 + (1/x)} + 1} \\ &= \frac{1}{\sqrt{1 + \lim\limits_{x \to \infty}(1/x)} + 1} \\ &= \frac{1}{1 + 1} \\ &= \frac{1}{2}\end{aligned}[/tex].

caylus

Answer:

Hello,

Step-by-step explanation:

[tex]\displaystyle \lim_{x \to \infty} \sqrt{x}*(\sqrt{x+1}-\sqrt{x} ) \\\\\\= \lim_{x \to \infty}\dfrac{ \sqrt{x}*(\sqrt{x+1}-\sqrt{x} )*(\sqrt{x+1}+\sqrt{x} )}{\sqrt{x+1} +\sqrt{x} } \\\\= \lim_{x \to \infty} \dfrac{\sqrt{x} *1}{\sqrt{x+1} +\sqrt{x} } \\\\\\= \lim_{x \to \infty} \dfrac{1} {\sqrt {\dfrac {x+1} {x} }+\sqrt{\dfrac{x}{x} } } \\\\\\=\dfrac{1} {\sqrt {1}+\sqrt{1} } \\\\\\=\dfrac{1} {2} \\[/tex]

ACCESS MORE